Effect of high-intensity interval training in young heart transplant recipients: results from two randomized controlled trials - Kari Nytrøen; Katrine Rolid; Marianne Yardley; Lars Gullestad (BMC, 2020)
Abstract Background Little is known about the effect of exercise in young heart transplant recipients, and results on group level is lacking. This study summarizes the findings of the youngest participants in two previous randomized controlled trials. Method This is a hypothesis-generating study reporting the main results from the youngest participants in two larger randomized controlled trials investigating the effect of high-intensity interval training (HIT). The article summarizes the main results from 28 young participants (< 40 year of age) who have participated in two previous studies which evaluated the effect of HIT vs. controls in adult heart transplant recipients. One of the studies included de novo heart transplant recipients and the other included maintenance heart transplant recipients. All study tests were performed in-hospital, in the specialist health care setting, but the exercise intervention was carried out locally, in cooperation with the primary health care. In both studies the exercise intervention lasted for 9-12 months. In one study, HIT (85-95% of peak effort) was compared to controls (no specific intervention), and in the other study HIT was compared to moderate, continuous exercise (MICT, 60-80% of peak effort). The main outcome measure was peak oxygen uptake (VO2peak) and a secondary endpoint was muscle strength. Results The summarized findings from the youngest heart transplant recipients in these two studies demonstrated mainly that the improvement in peak oxygen uptake among the younger recipients (< 40 years) was much larger (4.7 vs. 1.2 ml/kg/min and 7.0 vs. 2.2 ml/kg/min) compared to the improvement among the older recipients (≥ 40 years), and in accordance with results from adult heart transplant populations: HIT, compared to MICT, induced the largest improvement in peak oxygen consumption, also in the younger heart transplant recipients. Conclusions These results suggest that young heart transplant recipients have a greater effect of HIT than of MICT and may also suggest that younger recipients benefit more from high-intensity interval training than their older co-patients. However, larger randomized studies focusing on the young heart transplant population is strongly needed to confirm this hypothesis. Trial registration Clinical trial registrations: NCT01796379 and NCT01091194 .